Structure inheritance strategy from MOF to edge-enriched NiFe-LDH array for enhanced oxygen evolution reaction - Wang, Bingqing; Han, Xu; Guo, Chong; Jing, Jin; Yang, Can; Li, Yaping; Han, Aijuan; Wang, Dingsheng; Liu, Junfeng (Applied catalysis. B, Environmental, 2021)
[Display omitted] •A structure inheritance strategy to synthesize edge-enriched nanostructures is reported.•An edge-enriched NiFe-LDH nanoarray with high OER activity is successfully synthesized.•The roles of the edges in NiFe-LDH for OER is unraveled. The rational design of advanced nanostructures for catalysts to fully expose the edge or corner sites is highly desirable to optimize their electrocatalytic performance. In this work, we report an edge-enriched (EE) NiFe-layer double hydroxide (LDH) nanoarray with abundant coordinatively unsaturated sites, which was synthesized by a structure inheritance strategy using metal-organic framework (MOF) nanosheet array as a structure-directing template. Impressively, the obtained EE-NiFe-LDH nanosheet array offers high electrocatalytic activity in oxygen evolution reaction (OER) with an overpotential of only 205 mV to reach a current density of 10 mA cm−2, outperforming all reported NiFe-LDH nanostructures. X-ray absorption spectroscopy and density functional theory calculations demonstrate that the exposed edges in EE-NiFe-LDH contain abundant iron and oxygen vacancies, which optimized the electronic state of the NiFe-LDH and enhanced the adsorption of oxygenated intermediates, resulting in the high catalytic activity for OER.